Skill-biased technological change, training, and the college wage premium: A quantitative analysis - Thomas Palmer (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
This paper establishes that the rise in employer-provided training due to technological change has dampened the college wage premium. Using unique survey micro-data, I show that hightechnology firms provide more training overall, but the gap in training participation between high- and low-skill workers is smaller within these firms. To understand the aggregate implications of these patterns, I build a quantitative model of the labor market with endogenous technology and training investments. In a counterfactual exercise, I find that the increase in the college wage premium would be 63 percent greater if training costs remained constant between 1980 and the early 2000s.
Keywords: E24; I24; J24; J31; M53; O33; 330; Training; Technological Change; College Wage Premium; Education; Technology